2021
DOI: 10.1021/acs.macromol.1c00959
|View full text |Cite
|
Sign up to set email alerts
|

Decisive Influence of Hydrophobic Side Chains of Polyesters on Thermoinduced Gelation of Triblock Copolymer Aqueous Solutions

Abstract: A series of amphiphilic triblock copolymers composed of poly(ethylene glycol) (PEG) and poly(ε-caprolactone-co-5-alkyl δlactone)s bearing distinct alkyl side groups were synthesized via ringopening copolymerization of ε-caprolactone and a small amount of various 5-alkyl δ-lactones using PEG as the macroinitiator and metalfree diphenyl phosphate as the catalyst. The analysis of 1 H NMR, GPC, DSC, and XRD confirmed that the synthetic copolymers had similar molecular weights and bulk properties; nevertheless, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…[ 65 ] The T gel 's of BK‐Gel and NO‐Gel were 35 °C and 34 °C, respectively. Consistent with previous studies, [ 52,53 ] the temperature‐responsive gelation of BK‐Gel/NO‐Gel should be ascribed to the formation of a percolated micelle network driven via micellar aggregation (Figure 3C,D; Figures S6 and S7, Supporting Information). Meanwhile, after modification with NEAA, NO‐PLGA‐PEG‐PLGA‐NO copolymers seemed to be more hydrophobic than PLGA‐PEG‐PLGA copolymers, which made NO‐micelles more prone to aggregate upon heating (Figure 3D), resulting in a 1 °C decrease in T gel of NO‐Gel.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…[ 65 ] The T gel 's of BK‐Gel and NO‐Gel were 35 °C and 34 °C, respectively. Consistent with previous studies, [ 52,53 ] the temperature‐responsive gelation of BK‐Gel/NO‐Gel should be ascribed to the formation of a percolated micelle network driven via micellar aggregation (Figure 3C,D; Figures S6 and S7, Supporting Information). Meanwhile, after modification with NEAA, NO‐PLGA‐PEG‐PLGA‐NO copolymers seemed to be more hydrophobic than PLGA‐PEG‐PLGA copolymers, which made NO‐micelles more prone to aggregate upon heating (Figure 3D), resulting in a 1 °C decrease in T gel of NO‐Gel.…”
Section: Resultssupporting
confidence: 90%
“…First, the critical micelle concentrations (CMCs) of the two polymers were determined via the solubilization method of a hydrophobic probe, 1,6‐diphenyl‐1,3,5‐hexatriene (DPH). [ 52 ] The results showed that the two samples had a similar CMC (ca. 4.0 × 10 –4 g mL −1 ) at room temperature (Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This principle is applied to detect CMC. [ 39 ] According to Boltzmann fitting (Figure 3D), the addition of nicotinamide had no significant influence on the CMCs of the amphiphilic copolymer chains in water.…”
Section: Resultsmentioning
confidence: 99%